2020
DOI: 10.3390/foods9121830
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Volatilomic Fingerprint from Apple Fruits to Ciders: A Useful Tool to Find Putative Biomarkers for Each Apple Variety

Abstract: Aroma is a crucial criterion to assess the quality of apple fruits, juices, and ciders. The aim of this study was to explore similarities and differences in volatile profiles among apple fruits, juices, and ciders from different apple varieties (Festa, Branco, and Domingos) by headspace solid-phase microextraction gas chromatography–mass spectroscopy (HS–SPME/GC–MS). A total of 142 volatile organic compounds (VOCs) were identified, but only 9 were common in all analysed matrices and apple-tested varieties. Est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…The monoterpene alcohols linalool and dihydromyrcenol are often detected together in GC-based analysis, and contribute to the flowery and citrus aromas in wines [87]. Previous research has found that the concentration of linalool is influenced by the yeast strain [14] and the apple variety used in the fermentation of cider [19]. Dihydromyrcenol has not been previously reported in cider; however, it is typically found in blackcurrants, where it is responsible for their citrus and herbal aromas [87].…”
Section: Monoterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…The monoterpene alcohols linalool and dihydromyrcenol are often detected together in GC-based analysis, and contribute to the flowery and citrus aromas in wines [87]. Previous research has found that the concentration of linalool is influenced by the yeast strain [14] and the apple variety used in the fermentation of cider [19]. Dihydromyrcenol has not been previously reported in cider; however, it is typically found in blackcurrants, where it is responsible for their citrus and herbal aromas [87].…”
Section: Monoterpenesmentioning
confidence: 99%
“…Ciders from two of the apple varieties (Antei and Melba) showed quite distinct VOC profiles, while those from two other varieties (Kulikovskoye and Orlovski Sinap) showed very similar VOC profiles to one another and could not be discriminated. Medina, et al [19] was able to use the volatile composition of Portuguese ciders as a biomarker for the apple variety used. However, there is limited information available on the commonality of VOC profiles within commercial cider products produced by a single manufacturer, who may use different apple varieties but with the same cider manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in general saffron profiles of VOCs have not been comprehensively characterized, likely due to the complexity of the volatile fraction. Currently, the food-quality program of the European Union promotes food-origin protection through PDO and Protected Geographical Indication (PGI) to preserve biodiversity and ensure quality of the final product [6]. The increased interest for safranal and its related volatile compounds, as both aroma compounds and rewarding pharmacological agents, prompted us to undertake research on Campania saffron to determine simultaneously the amount of safranal and related volatile compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, EHX treatment remarkably suppressed CVB3 replication and improved the overall condition and survival of virus-infected mice. Because EHX is a naturally occurring compound in fruits, food additives, and vegetables ( Dunkel et al, 2009 ; Medina et al, 2020 ), the treatment of CVB-related infections with EHX can be well tolerated. Nonetheless, results from the animal model do not necessarily predict replication in human trials ( Bracken, 2009 ); it is worthy of further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we reported the antiviral activity of ethyl 3-hydroxyhexanoate (EHX). EHX is a fatty acid ethyl ester of 3-hydroxyhexanoic acid, a key volatile compound in several fruits, such as pineapples, orange juice, cape gooseberry, wood apples, citrus flesh, grapes, tamarillos, and caja fruits ( Dunkel et al, 2009 ; Garg et al, 2018 ; Medina et al, 2020 ). The safety evaluations of EHX have received the approval of Joint Food and Agricultural Organization of the United States/World Health Organization Expert Committee on Food Additives ( Food and Agriculture Organization of the United Nations [FAOUN], 2002 ).…”
Section: Introductionmentioning
confidence: 99%